2012
DOI: 10.1021/ja209044g
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Synthesis of Mesoporous Pt–Au Binary Alloys with Tunable Compositions for Enhancement of Electrochemical Performance

Abstract: Mesoporous Pt-Au binary alloys were electrochemically synthesized from lyotropic liquid crystals (LLCs) containing corresponding metal species. Two-dimensional exagonally ordered LLC templates were prepared on conductive substrates from diluted surfactant solutions including water, a nonionic surfactant, ethanol, and metal species by drop-coating. Electrochemical synthesis using such LLC templates enabled the preparation of ordered mesoporous Pt-Au binary alloys without phase segregation. The framework composi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
192
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 246 publications
(194 citation statements)
references
References 82 publications
1
192
0
1
Order By: Relevance
“…They usually demonstrate higher catalytic activity, faster response rate, and better resistance to deactivation for various chemical processes [3,4], which are ascribed to electronic (ligand) effects and/or geometric effects caused by the surface atomic environment of distinct metal atoms [5][6][7]. In recent years, a variety of intriguing strategies have been designed to prepare alloy nanoparticles, such as laser ablation [8], cathodic corrosion [9], chemical reduction [10,11], salt impregnation [12], colloidal synthesis [13], and dendrimer templating method [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They usually demonstrate higher catalytic activity, faster response rate, and better resistance to deactivation for various chemical processes [3,4], which are ascribed to electronic (ligand) effects and/or geometric effects caused by the surface atomic environment of distinct metal atoms [5][6][7]. In recent years, a variety of intriguing strategies have been designed to prepare alloy nanoparticles, such as laser ablation [8], cathodic corrosion [9], chemical reduction [10,11], salt impregnation [12], colloidal synthesis [13], and dendrimer templating method [14].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, a variety of intriguing strategies have been designed to prepare alloy nanoparticles, such as laser ablation [8], cathodic corrosion [9], chemical reduction [10,11], salt impregnation [12], colloidal synthesis [13], and dendrimer templating method [14]. These methods are helpful for the study of alloy nanomaterials, while relatively time-consuming operations, complicated experimental conditions, or surface contamination arising from surfactant are commonly involved, which hinder their further applications [3,5].…”
Section: Introductionmentioning
confidence: 99%
“…For example, the electrocatalytic reaction is kinetically limited, the low CO poisoning tolerance causes severe durability of catalyst, and the scale of Pt catalysts leads to high cost. [6][7][8][9][10] To address these issues, many recent efforts have been devoted to synthesizing Pt-M bimetallic electrocatalysts (where M ¼ Pd, Co, Ni, Fe, Au, Cu, and so on). [11][12][13][14][15][16] The bimetallic Pt-based electrocatalysts have unusual electronic structures and arrangements of surface atoms in the near-surface region, and accordingly exhibit improved electrocatalytic activity and cycle stability compared with the monometallic Pt.…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon may explain the volcano-type dependence of PtAuCu-AA NTs. What is particularly worth mentioning is that Yamauchi et al [54] reported similar result that the Pt 90 Au 10 binary alloys show best stability.…”
Section: Articlesmentioning
confidence: 77%